2002
DOI: 10.1046/j.0022-202x.2001.01682.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Abnormalities of the P15 and P16 Genes in Mycosis Fungoides and Sezary Syndrome

Abstract: There are few data on the molecular pathogenesis of cutaneous T cell lymphomas. A recent allelotyping study by our group identified frequent allelic loss on 9p, 10q, and 17p including losses on 9p21 in 16% of patients with mycosis fungoides and 46% with Sezary syndrome. The P15 and P16 genes are intricately linked on 9p21 and can be inactivated in melanoma and non-Hodgkin's lymphoma. We have therefore studied 76 patients with either mycosis fungoides or Sezary syndrome for abnormalities of these genes. DNA sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 54 publications
(69 reference statements)
2
73
1
3
Order By: Relevance
“…Therefore, combined deletion of CDKN2A/CDKN2B or their epigenetic silencing, leads to RB1 phosphorylation and loss of p53, culminating in cell-cycle progression. These abnormalities are frequently observed in CTCL, suggesting their early involvement in disease pathogenesis [92,93]. Cyclin upregulation, including cyclinD1, and loss of RB1 have also been described [94].…”
Section: Immunopathogenesismentioning
confidence: 92%
“…Therefore, combined deletion of CDKN2A/CDKN2B or their epigenetic silencing, leads to RB1 phosphorylation and loss of p53, culminating in cell-cycle progression. These abnormalities are frequently observed in CTCL, suggesting their early involvement in disease pathogenesis [92,93]. Cyclin upregulation, including cyclinD1, and loss of RB1 have also been described [94].…”
Section: Immunopathogenesismentioning
confidence: 92%
“…22 Interestingly, no point mutation of either p16 INK4A or p15 INK4B genes was found, but aberrant 5 0 -CpG island methylation of either p16 INK4A and/or p15 INK4B , but not of p14 ARF , was detected. [21][22][23] In SS, selective hypermethylation of p15 INK4B but not p14 ARF or p16 INK4A was observed in 42% of cases, 21,24 a pattern not seen in aggressive mycosis fungoides. 22 Using enrichment in tumor cells by microdissection of 25 skin samples, LOH was similarly observed in two out of 15 plaque-stage mycosis fungoides and in two out of 10 tumor-stage mycosis fungoides.…”
Section: And Gil and Peters 5 )mentioning
confidence: 95%
“…Using microsatellite markers surrounding the CDKN2A-CDKN2B locus, loss of heterozygosity (LOH), suggesting either hemizygous or homozygous deletion, was indeed detected equally in the early and late stages of mycosis fungoides (21%) and SS (37%) cases (25% of epidermotropic CTCL). 21 Another group suggested that LOH or homozygous deletion was not present in patients with early-stage and stable mycosis fungoides (n ¼ 21), but appeared during the tumoral progression of mycosis fungoides (3 out of 11 samples). 22 Interestingly, no point mutation of either p16 INK4A or p15 INK4B genes was found, but aberrant 5 0 -CpG island methylation of either p16 INK4A and/or p15 INK4B , but not of p14 ARF , was detected.…”
Section: And Gil and Peters 5 )mentioning
confidence: 99%
“…[15][16][17][18][19] However, our findings suggest that p16 gene methylation is not associated with the tumor progression but rather may contribute to the 35,36 and by the frequent p16 gene methylation found in monoclonal gammopathy of undetermined significance, in the plaque phase of mycosis fungoides, and in other premalignant lesions. [20][21][22]37 Several MALT lymphoma-specific or -associated gene alterations have been reported, such as translocations between the immunoglobulin heavy chain gene and BCL10 gene or MALT1 gene, trisomy 3, and trisomy 18, as well as API2-MALT1 fusion. 38 These seem to be mutually exclusive, and constitute up to 80% of the pulmonary MALT lymphoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] However, it has also been suggested that the methylation of this gene is one of the early events in the development of lymphoid malignancies. [20][21][22] MALT lymphoma constitutes more than 80% of all primary lung lymphomas. 23 It should be noted that the involvement of API2-MALT1 fusion is particularly high (up to half of all cases) in pulmonary MALT lymphoma compared with MALT lymphomas at other sites, 24 and may define a distinctive clinicopathologic subgroup of pulmonary MALT lymphomas.…”
mentioning
confidence: 99%